Using Ancient DNA Analysis and Radiocarbon Dating to Determine the Provenance of an Unusual Whaling Artifact - Caitlin Mudge; Rebecca Dallwitz; Bastien Llamas; Jeremy J. Austin (Frontiers in Ecology and Evolution, 2020)
Natural history collections provide a critical temporal view of past biodiversity and are instrumental in the study of extinct populations. However, the value of historical specimens relies on correct species identification, collection date and collection locality. The Australian National Maritime Museum (ANMM) holds an unusual artifact – an electric lamp made from a dried whale penis – with unknown age, species-of-origin and collection locality. We used ancient DNA methods to generate a partial mitochondrial DNA (mtDNA) genome sequence to establish the identity and provenance of the whale, and accelerator mass spectrometry (AMS) radiocarbon dating to determine the approximate year of death. Mitochondrial DNA sequences from the 16S rRNA gene and the control region indicate that the specimen belonged to a sperm whale (Physeter macrocephalus) and a modern radiocarbon age suggests it was collected post-1950s. We were unable to determine the collection locality of the whale due to the very broad geographic distribution of its mtDNA haplotype. Our results suggest the specimen was possibly collected as a souvenir during post-war whaling, where nearly 30,000 male sperm whales were killed annually. This study supports and extends previous research that applies ancient DNA and radiocarbon dating techniques to enhance the value of natural history collections, by identifying the species-of-origin and age of historical specimens.